An authentication and key agreement mechanism for OPC Unified Architecture in industrial Internet of Things - Min Wei; Shuaidong Zhang; Ping Wang; Keecheon Kim (International Journal of Distributed Sensor Networks)
As an industrial communication data interaction specification, OPC Unified Architecture effectively solves the industrial Internet of Things system integration problem. This article designs an authentication and key agreement scheme based on implicit certificate using the security model provided by OPC Unified Architecture. It establishes the secure channel and provides a guarantee for secure session for the OPC Unified Architecture server and client. Then, the test verification platform is implemented to verify the feasibility of the scheme. The result shows that the mechanism is feasible, and the system security and availability are effectively improved.